Digital Content Model as A Basis of Connectives Knowledge Learning For Digital Society - Sulianta, Feri; Sapriya,; Supriatna, Nana; Disman, (International Journal of Psychosocial Rehabilitation, 2020)
Today's learning for competency civics, is very dependent on information technology, which is a form of learning theory of Connectivity, where knowledge is no longer on individuals but outside individuals who are enabled by information technology devices that are able to manage knowledge and organize knowledge on complex cyber networks on the internet. Students and digital society today are very dependent on this type of learning, in getting information, managing, and storing or publishing information.For this reason, a digital content model was developed using the research and development method proposed by Borg and Gall consists of ten steps, namely: research & study of literature, product design, design validation, product manufacture, initial product testing, product revision, product testing large scale, product revision, product specifications, and dissemination.The model was created using six components, namely: Digital Media, Writing Method, Search Engine Optimization, Social Studies Education, Knowledge, Digital Copyright. Large-scale testing is compared from pre-test and post-test, while this teaching produces digital content reported on the User generated Content Platform. This digital learning is effective with achievement. The implementation of this digital content model shows a significant change regarding digital literacy competency which effectively increases digital literacy competence by 34.56% by approaching connectivity.